Implementation of Total Quality Management and its impact to Madrasah Aliyah (Islamic Senior High School) - Busahdiar, Busahdiar; Arief, Armai; Karimah, Ummah; Taufiqurrahman, Hafidz; Rahman, Ariq Fadillah (IAIN Salatiga, 2023)
There is a pillar that stimulates total quality management as a reference for education institution manager in adopting TQM. Field study was conducted in this research using a descriptive qualitative approach through case study. Interviews, documentation, and observation were employed to collect field data. Data analysis techniques used in this research included data reduction and conclusion drawing. Data Triangulation was used to validate the data. The author obtained data from the Principal, Vice Principal, Head of School Administration, Head of Committee, teachers, students, and some alumni of MAN 4 Pondok Pinang South Jakarta, whom the author considers to have representative values to reach the data. The research findings show that this school has implemented the ISO-9001:2008 Quality Management System. It reflects that, this madrasah has been managed well approved with its various achievements achieved by MAN 4 Model from local and national levels. Thus, it has an impact on students and teachers who are responsible for these achievements. Moreover, this school has integrated modern administration, especially for outside relation or stakeholders. Thus, the application of TQM affects on stakeholders' satisfaction on the increasing students' achievement and staff excellent service.